Retaining Special Educators with Autism Expertise in Schools - Hall, Laura J.; Pavez, Beth Allison (Journal of the American Academy of Special Education Professionals, 2023)
At a time when there is an increase in prevalence of autism spectrum disorder (ASD), creating a high demand for professionals who have knowledge and skills in the use of evidence-based practices identified for students with ASD, there is also a severe shortage of special educators in our schools. Teacher attrition is a significant contributor to this shortage. Therefore, it is important to determine the factors that support the retention of special educators with a specialization in autism who have a choice of employment options. This study surveyed graduates of an M.A. Degree/Autism specialization program who identified the factors they sought in a position. Results from this study indicate that providing professional development opportunities and support for leadership positions may impact the retention of highly skilled personnel.